2014
DOI: 10.1016/j.rboe.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the acromial curvature and its relationships with the subacromial space and types of acromion

Abstract: ObjectiveTo correlate the acromial curvature, using the angles proposed, with the subacromial space and types of acromion.MethodsNinety scapulas were studied. The acromia were classified as types I, II or III. The acromial curvature was analyzed by means of the alpha, beta and theta angles. We also measured the distance between the anteroinferior extremity of the acromion and the supraglenoid tubercle (DA). The scapulas were grouped in relation to sex and age. The angles proposed were analyzed in relation to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…Accordingly, acromioplasty would be beneficial for SAIS patients who had hooked acromion. SAD has a relationship with SAIS since impingement usually occurs vertically [35]. AT is also an important parameter affecting the vertical dimension of subacromial space.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, acromioplasty would be beneficial for SAIS patients who had hooked acromion. SAD has a relationship with SAIS since impingement usually occurs vertically [35]. AT is also an important parameter affecting the vertical dimension of subacromial space.…”
Section: Discussionmentioning
confidence: 99%
“…Korakoakromial arktaki patolojiler bu anatomik bölgenin varyasyonları ve morfolojisi ile ilişkilidir (8). Bigliani ve ark.…”
Section: Tartışma Ve Sonuçunclassified
“…Literatürdeki çoğu çalışma kadavralar ve gönüllüler üzerinde yapılmış olup genellikle X-Ray çalışmalarıdır. Kadavra ve gönüllü ile yapılan çalışmalarda vaka sayıları az olmakta ve bu hasta grupları ile supraspinatus patolojileri değerlendirilememektedir (1,3,5,8). X-Ray ile akromion morfolojisini değerlendirmenin sensivitesinin düşük olduğu (12), MRI ile akromion tiplendirmesi, akromiyal morfolojinin belirlenmesinde X-Ray gibi geçerli bir yöntem olduğu (13) farklı yazarlar tarafından dile getirilmiş olup MRI için farklı bir sınıflandırmaya ihtiyaç duyulmamıştır.…”
Section: Tartışma Ve Sonuçunclassified
“…In 1996, Getz et al evaluated acromial shape by objective method and reported 22.8% type I; 68.5% type II and 8.6% type III acromion processes. 6 Many other authors Yazici et al, 7 Shah et al, 8 Nigar et al, 9 Natsis et al, 10 Paraskevas et al, 11 Collipal et al, 12 Jose et al 13 and Naidoo et al 14 also evaluated acromion processes among different other population group through dry scapulae.…”
Section: Introductionmentioning
confidence: 99%